2020
DOI: 10.3390/app10010349
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of an Extracellular Polymeric Substance from Earthworm Gut Bacterium (Bacillus licheniformis) for Bioflocculation and Heavy Metal Removal Potential

Abstract: The present study shows the potential of an extracellular polymeric substance (EPS) produced by Bacillus licheniformis strain KX657843 isolated from earthworm (Metaphire posthuma) gut in the sorption of Cu(II) and Zn(II) and in flocculation. After harvesting bacterial cells from sucrose supplemented denitrifying culture medium, the EPS was extracted following ethanolic extraction method. The Fourier Transform Infrared Spectroscopy (FTIR) and 1H and 13C Nuclear Magnetic Resonance (NMR) of EPS revealed its funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 45 publications
(103 reference statements)
0
14
0
Order By: Relevance
“…These negatively charged functional groups are responsible for the high-negative zeta potential of this EPS, which was À33.83 mV. 30,37 Busi et al, 9 Shi et al 29 and Biswas et al 38 reported that EPS contained abundant charged functional groups, especially amino and carboxyl groups that might have been mainly responsible for the ability of the studied EPS to bind metal ions and to act as flocculants. EPS could act as biosorbents to efficiently remove heavy metals and as thickening, gelling and emulsifying agents…”
Section: Chemical Compositionmentioning
confidence: 87%
“…These negatively charged functional groups are responsible for the high-negative zeta potential of this EPS, which was À33.83 mV. 30,37 Busi et al, 9 Shi et al 29 and Biswas et al 38 reported that EPS contained abundant charged functional groups, especially amino and carboxyl groups that might have been mainly responsible for the ability of the studied EPS to bind metal ions and to act as flocculants. EPS could act as biosorbents to efficiently remove heavy metals and as thickening, gelling and emulsifying agents…”
Section: Chemical Compositionmentioning
confidence: 87%
“…B. licheniformis is a Gram-positive, motile, non-pathogenic bacterium ubiquitously spread in natural habitats. As it is associated with plant material, it can be easily isolated from soil, water and the rhizosphere [ 1 , 23 , 24 , 25 , 26 ], but it can also be found on the feathers of terrestrial and aquatic bird species, and in marine water [ 27 ]. B. licheniformis is widely used in industry, horticulture and pharmacy.…”
Section: Introductionmentioning
confidence: 99%
“…EPS reported the metal removal potential of 54% and 42% at pH 5, which increases considerably to 86% and 81% at pH 8 for Cu (II) and Zn (II), respectively, at a metal concentration 25 mg/L in solution. The overall metal removal efficiency of 94.8% for both metals are observed at 100 mg/L EPS concentration [ 109 ]. Generally, through electrostatic interactions, the carbohydrate and protein moieties in EPS are furnished with their metal-binding properties and binds with cations.…”
Section: Potential Environmental Applicationsmentioning
confidence: 99%